Becoming readers and writers : literate identities across childhood and adolescence (New York, NY : Routledge, 2024)
"Centered around the idea that literacy teaching is more the transmission of strategies and skills, this volume serves as a foundation for approaching literacy from an identity perspective. Through incisive and accessible chapters from top scholars, it introduces readers to the concept of literate identities, examining them across ages and grade levels to present an overview of how scholars and educators can use this concept in their research and teaching in literacy contexts. Organized by developmental level with sections on early childhood, middle childhood, adolescence, and cross-age research, contributors reveal how literacy can be framed as an identity practice to engage students and support their development. Applying a range of theoretical perspectives and frameworks, each chapter identifies the identity theory used, explains the relevant methodology and research questions, covers implications for practice, and includes questions or prompts for discussion. Addressing key topics, including culturally relevant pedagogy, intersectionality, and transnationalism, the volume reveals how understanding literate identities is at the heart of effective and inclusive literacy instruction. Illuminating multiple pathways to understanding students as readers and writers, this book is essential for pre-service teachers, scholars and researchers in literacy education, research methods, and multicultural education"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Language arts -- Psychological aspects; Literacy -- Social aspects; Identity (Psychology) in education